The hero with a thousand faces - Campbell, Joseph, 1904-1987.; Joseph Campbell Foundation (Novato, CA : New World Library, 2008)
Examines myths and folk tales from around the world in an attempt to understand the symbolism of the hero as it appears in the mythologies and religions of mankind.
"Joseph Campbell Foundation.".
Includes bibliographical references (p. 341-382) and index.
Adult
Keywords: Mythology; Psychoanalysis; Mythology; Psychoanalysis